Corrosion Studies of Nanostructured AlN Coating Deposited on 23/8N Nitronic Steel by PVD Method. (2017) - Shukla, V.N.; saini, Himanshu; Kumar, Devendra; Gupta, Gaurav
Abstract: The microstructure properties and degradation behavior of nanostructured Aluminium Nitride (AlN) coating deposited on 23/8N Nitronic steel by Physical Vapour Deposition Technique (PVD) subjected to oxidation in molten salt [Na2 SO4 -25NaCl] environment at 700 °C for 50 hours has been carried out in the present work. The morphologies and scale of the coatings were characterized by using Fe-Sem microscopy/ energy dispersive analysis. The coatings have uniform microstructure. It is evident from the microstructure that the coatings has some pores and inclusions. The coating thickness for as coated AlN coatings is 2µm±1µm. The average grain size of AlN coatings is 16 nm. The results obtained showed the better performance of AlN coated specimens as compare to bare substrate.